Haksız fiilden ve sözleşmeden doğan sorumluluk çerçevesinde sebeplerin yarışması (tbk m. 60) - Tosun, Çağdaş (My University, 2019)
Tazminat talebine dayanak oluşturan hukuki sebep, hem haksız fiilden hem de sözleşmeye aykırılıktan kaynaklanabilir. Türk Borçlar Kanunu m. 60 hükmü kapsamında bu hukuki sebeplerin yarışması durumunda, zarar gören için en iyi giderim imkanı sağlayan sorumluluk sebebinin tespit edilmesi ile zarar görenin aksini istemiş olması halinin yorumlanması önem arz etmektedir. Sorumluluk sebeplerinin yarışması durumunun medeni yargılamaya hakim olan ilkelerden bağımsız olarak ele alınması düşünülemez. Bu kapsamda haksız fiilden doğan sorumluluk ile sözleşmeden doğan sorumluluğun yarışması ele alınmış ve bu durum medeni yargılama hukukuna hakim olan ilkeler ışığında değerlendirilmiştir.

The legal reason that constitutes the basis for the claim for compensation may result from both the tort and the breach of contract. In the event that these legal reasons compete under the provisions of Article 60 of the Turkish Code of Obligations, it is important to determine the reason for the liability that provides the best remedy for the aggrieved person and to interpret of the condition that the aggrieved person has requested the opposite. It cannot be considered that the status of the competition for reasons of liability can be handled independently of the principles prevailing in civil proceedings. In this context, competition of the liability arising from the tort with the liability arising from the contract are discussed and this situation is evaluated in the light of principles prevailing in law of civil judgement.
Keywords: Article 60 of the Turkish Code of Obligations; Civil law; Competition of demands; Competition of reasons; Competition of rights; Hakların yarışması; Haksız fiilden doğan sorumluluk; Hukuk; Law; Liability arising from contract; Medeni hukuk; Medeni yargılama hukukuna hakim olan ilkeler Liability arising from tort; Principles prevailing in law of civil judgement; Sebeplerin yarışması; Sözleşmeden doğan sorumluluk; Taleplerin yarışması; Türk Borçlar Kanunu m. 60